2015
DOI: 10.1007/s00423-015-1310-2
|View full text |Cite
|
Sign up to set email alerts
|

Staged resection of bilobar colorectal liver metastases: surgical strategies

Abstract: In selected patients, two-stage hepatectomy and ALPPS are efficient and safe to convert unresectable to resectable CLM. Further studies are required to evaluate long-term outcome of these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
0
6
0
5
Order By: Relevance
“…At present, hepatic resection is the only proven surgical procedure for curative purposes. With this intervention, operative mortality rates as low as 1e2% can be achieved [42,43]. Further, according to the evidence, an increasing number of elderly patients are presenting with CRC and being referred for surgical resection of LM [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…At present, hepatic resection is the only proven surgical procedure for curative purposes. With this intervention, operative mortality rates as low as 1e2% can be achieved [42,43]. Further, according to the evidence, an increasing number of elderly patients are presenting with CRC and being referred for surgical resection of LM [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that big tumours (>3cm), multiple metastases and non-anatomic (84,85). However, several studies have shown that in selected patients, similar outcomes can be achieved performing one-or two-stage liver resection (86)(87)(88)(89).…”
Section: Long-term Oncological Outcomes After Lpslr For Crlmmentioning
confidence: 99%
“…In particular, two-stage hepatectomy (TSH) with or without interstage chemotherapy, as well as portal vein embolization (PVE) of the contralateral lobe, is currently in use [1113]. Waiting time between the two procedures is 8–12 weeks and 4–6 weeks after TSH and PVE, respectively [14]. Although significant improvement of resectability has been achieved with these techniques, a number of patients remain irresectable either because of an inappropriate increase in FLR or because of tumor progression during the waiting period until resection [13, 15, 16].…”
Section: Introductionmentioning
confidence: 99%